Hospitalisations related to administration errors of psychotropic drugs: a nationwide retrospective study between 1998 and 2019 in Australia - Alsaleh, Fatemah M.; Naser, Abdallah Y.; Alsairafi, Zahra K.; Ofori-Asenso, Richard (Frontiers in Pharmacology, 2023)
Objectives: Medication administration error occurs when there is a discrepancy between what the patient received or was planned to receive and what the doctor originally intended. The aim of this study was to examine the trends in hospitalisation related to administration errors of psychotropic drugs in Australia. Materials and Methods: This was a secular trend analysis study that examined the hospitalisation pattern for medication administration errors of psychotropic drugs in Australia between 1998 and 2019. Data on medication administration errors of psychotropic drugs was obtained from The National Hospital Morbidity Database. We analysed the variation in hospitalisation rates using the Pearson chi-square test for independence. Results: Hospitalisation rates related to administration errors of psychotropic drugs increased by 8.3% [from 36.22 (95% CI 35.36—37.08) in 1998 to 39.21 (95% CI 38.44—39.98) in 2019 per 100,000 persons, p < 0.05]. Overnight-stay hospital admission patients accounted for 70.3% of the total number of episodes. Rates of same-day hospitalisation increased by 12.3% [from 10.35 (95% CI 9.90—10.81) in 1998 to 11.63 (95% CI 11.21—12.05) in 2019 per 100,000 persons]. Rates of overnight-stay hospital admission increased by 1.8% [from 25.86 (95% CI 25.13—26.59) in 1998 to 26.34 (95% CI 25.71—26.97) in 2019 per 100,000 persons]. Other and unspecified antidepressants (selective serotonin and norepinephrine reuptake inhibitors) were the most common reason for hospitalisation accounting for 36.6% of the total number of hospitalisation episodes. Females accounted for 111,029 hospitalisation episodes, representing 63.2% of all hospitalisation episodes. The age group 20–39 years accounted for nearly half (48.6%) of the total number of episodes. Conclusion: Psychotropic drug administration error is a regular cause of hospitalization in Australia. Hospitalizations usually required overnight stays. The majority of hospitalizations were in persons aged 20–39 years, which is concerning and warrants further investigation. Future studies should examine the risk factors for hospitalization related to psychiatric drug administration errors.